PENGARUH BOOK-TAX DIFFERENCE TERHADAP PERTUMBUHAN LABA (Studi Empiris Terhadap Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di BEI Pada Tahun 2017-2020) - Jesica Gabriela Simanjuntak; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study is conducted to research the effect of book-tax difference on profit growth in manufacturing companies. This research was aimed at the food and beverages company which was listed on the lndonesia Stock Exchange in 2017-2020. The data used for this study is reserve from annual financial statement and used descriptive with a quantitative approach as the research method. Based on the partial and stimultaneous test, results that book-tax difference that outlined by permanent difference and temporary difference have significant effect on profit growth.